2018
DOI: 10.1111/jfd.12790
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tilapia lake virus (TiLV) infection by PCR in farmed and wild Nile tilapia (Oreochromis niloticus) from Lake Victoria

Abstract: Tilapia lake virus disease (TiLVD) has emerged to be an important viral disease of farmed Nile tilapia (Oreochromis niloticus) having the potential to impede expansion of aquaculture production. There is a need for rapid diagnostic tools to identify infected fish to limit the spread in individual farms. We report the first detection of TiLV infection by PCR in farmed and wild Nile tilapia from Lake Victoria. There was no difference in prevalence between farmed and wild fish samples (p = .65), and of the 442 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
78
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 31 publications
3
78
1
2
Order By: Relevance
“…Tissue distribution of TiLV by RT‐PCR assay revealed its presence in all the organs tested in naturally and experimentally infected O. niloticus and O. mossambicus . Our observation regarding the presence of TiLV in spleen, liver, brain, heart, abdominal muscle, gill, kidney, intestine and eye of Mozambique tilapia by RT‐PCR agrees with the observation made by Dong et al () and Mugimba et al () whose reports revealed the presence of TiLV in all the organs of Nile tilapia by in situ hybridization and RT‐PCR. A knowledge of the tissue distribution of pathogen in the host can help us to understand issues related to disease susceptibility, tissue damage caused by the pathogen, transmission, selection of organ for pathogen isolation and detection, and development of control measures.…”
Section: Discussionsupporting
confidence: 92%
“…Tissue distribution of TiLV by RT‐PCR assay revealed its presence in all the organs tested in naturally and experimentally infected O. niloticus and O. mossambicus . Our observation regarding the presence of TiLV in spleen, liver, brain, heart, abdominal muscle, gill, kidney, intestine and eye of Mozambique tilapia by RT‐PCR agrees with the observation made by Dong et al () and Mugimba et al () whose reports revealed the presence of TiLV in all the organs of Nile tilapia by in situ hybridization and RT‐PCR. A knowledge of the tissue distribution of pathogen in the host can help us to understand issues related to disease susceptibility, tissue damage caused by the pathogen, transmission, selection of organ for pathogen isolation and detection, and development of control measures.…”
Section: Discussionsupporting
confidence: 92%
“…The disease caused by TiLV was first reported in Israel in 2009, while the virus was first characterized in 2014 [1]. Since then, TiLV infections have been reported from different countries around the world [2][3][4][5]. It is an icosahedral virus made of a trilaminar capsid with a diameter of 55-110 nm, which is morphologically similar to orthomyxoviruses [1].…”
Section: Introductionmentioning
confidence: 99%
“…From literature, most of the work done on tilapia fish concerning TiLV had necessitated killing the fish to obtain coelomic organs (Amal et al, 2018;Behera et al, 2018;Mugimba et al, 2018;Senapin, Shyam, Meemetta, Rattanarojpong, & Dong, 2018). The major problem with lethal sampling for health monitoring and surveillance is that it may not be feasible in broodstock screening as a reduction in numbers equates to economic loss to the farmer (Cutrin et al, 2005).…”
mentioning
confidence: 99%